The Tomato Genome Encodes SPCH, MUTE, and FAMA Candidates That Can Replace the Endogenous Functions of Their Arabidopsis Orthologs - Ortega, Alfonso; de Marcos, Alberto; Illescas-Miranda, Jonatan; Mena, Montaña; Fenoll, Carmen (Frontiers in Plant Science, 2019)
Stomatal abundance determines the maximum potential for gas exchange between the plant and the atmosphere. In Arabidopsis, it is set during organ development through complex genetic networks linking epidermal differentiation programs with environmental response circuits. Three related bHLH transcription factors, SPCH, MUTE, and FAMA, act as positive drivers of stomata differentiation. Mutant alleles of some of these genes sustain different stomatal numbers in the mature organs and have potential to modify plant performance under different environmental conditions. However, knowledge about stomatal genes in dicotyledoneous crops is scarce. In this work, we identified the Solanum lycopersicum putative orthologs of these three master regulators and assessed their functional orthology by their ability to complement Arabidopsis loss-of-function mutants, the epidermal phenotypes elicited by their conditional overexpression, and the expression patterns of their promoter regions in Arabidopsis. Our results indicate that the tomato proteins are functionally equivalent to their Arabidopsis counterparts and that the tomato putative promoter regions display temporal and spatial expression domains similar to those reported for the Arabidopsis genes. In vivo tracking of tomato stomatal lineages in developing cotyledons revealed cell division and differentiation histories similar to those of Arabidopsis. Interestingly, the S. lycopersicum genome harbors a FAMA-like gene, expressed in leaves but functionally distinct from the true FAMA orthologue. Thus, the basic program for stomatal development in S. lycopersicum uses key conserved genetic determinants. This opens the possibility of modifying stomatal abundance in tomato through previously tested Arabidopsis alleles conferring altered stomata abundance phenotypes that correlate with physiological traits related to water status, leaf cooling, or photosynthesis.